Analisis Cita Rasa Kopi di Tilik Kopi Kota Padang - Rahman, Taufik; Susanti, Retnaningtyas; Wulansari, Nidia; Azwar, Hendri (CV. ITTC INDONESIA, 2024)
This research was motivated by customer reviews regarding the taste of coffee in Padang City Coffee. This research is classified as qualitative research with the method used being descriptive. The variables used in this research are coffee and taste. The research sample was 5 people, data was collected by distributing observations and interviews. The results of this research show that the aroma of the product presented is good with the criteria of a typical coffee aroma without the presence of the aroma of other ingredients such as chemicals. The acidity of the product presented is quite good with the typical criteria for coffee acid which has a pH of 4.85 to 5.10. The level of balance of taste of the product served is good because the coffee served has a taste that is formed due to the right mixture of ingredients. The level of viscosity of the product served is good by paying attention to the amount of ground coffee that will be processed with the water used using a dose of 1:2 with water. The bitter taste of the product served is very good because the bitterness produced is just right due to correct coffee processing, without any other causes such as bad coffee powder. The sweet taste of the product served is quite good according to consumer tastes. From all the aspects considered in this research, in general, espresso is better than Americano because espresso is the basis for making Americano itself.